Optimizing Online Content Instruction for Effective Hybrid Teacher Professional Development Programs - Clary, Renee M.; Dunne, James A.; Elder, Anastasia D.; Saebo, Svein; Beard, Debbie J.; Wax, Charles L.; Winter, Joshua; Tucker, Deborah L. (Journal of science teacher education, 2017)
The Teacher Academy in the Natural Sciences (TANS) provided middle school (U.S. Grades 6-8) teachers (N = 81) with intensive professional development in chemistry, geosciences, and physics through 13 days of face-to-face instruction that was extended with 2 online science modules per discipline. Because we administered online module assessments before the summer academy (pretest), after the summer academy (Post 1), and after the online module was assigned (Post 2), we were able to analyze via dependent t tests the learning components contributed by the online module. Only 1 geosciences module resulted in significant gains after it was assigned. Other modules (2 physics, 1 geosciences) resulted in gains before module assignments, at the end of the 10-day summer academy. Although the 2 chemistry modules exhibited positive score increases, no significant gains were made. Calculated Pearson correlation coefficients revealed no association between participants' online access times and science content gains. This research documents benefits of hybrid teacher professional development programs and offers recommendations for their optimized effectiveness, including more consistent instructor/participant online access.